Optimization of Personal Data Rights Protection in Artificial Intelligence Era Under Indonesia’s Cybersecurity Law. - Masudianto, Dwi Nugroho; Barthos, Megawati (Interdiciplinary Journal & Hummanity (INJURITY), 2025)
The absence of clear regulations on Artificial Intelligence (AI) in Indonesia's Law Number 27 of 2022 concerning Personal Data Protection (UU PDP) creates significant challenges in safeguarding personal data, particularly in automatic data processing, algorithm transparency, and accountability for AI-based decisions. This study aims to highlight the importance of strengthening personal data protection regulations in Indonesia, specifically focusing on the use of AI, and to propose improvements based on global best practices to ensure a balance between technological innovation and the protection of individual rights. The research uses a qualitative approach, examining the gaps in Indonesia’s PDP Law regarding AI through comparative analysis with international standards, particularly the EU's General Data Protection Regulation (GDPR). The study identifies several risks associated with the lack of regulation, including unauthorized data exploitation, algorithmic bias, and the black-box problem in AI-based decision-making. The absence of mechanisms for legal recourse in AI decisions further exacerbates these issues. In contrast, the GDPR provides guidelines for transparency and accountability in AI systems, which the Indonesian PDP Law lacks. Strengthening the regulation of AI within the personal data protection framework is crucial to ensuring fairness, transparency, and accountability. Adopting concepts such as Explainable AI (XAI) will help address the challenges posed by the rapid advancement of AI technologies. The findings suggest that Indonesia must revise the PDP Law to include provisions that regulate AI’s use of personal data, ensuring a more ethical and transparent approach to AI-based decision-making.